ANALISIS PENERAPAN ASUHAN PERSALINAN NORMAL (APN) OLEH BIDAN - Nurhayati Nurhayati; Men Eliza (Maternal Child Health Care, 2022)
The basis care in normal delivery is clean and safe care during and after the baby is born. They are efforts to prevent complications. The incidence of postpartum hemorrhage in Indonesia is estimated around 45% of all existing deliveries. Normal childbirth training is an effort to improve the competence of midwives in carrying out childbirth assistance. The purpose of this research was to find out the funds, motivation, facilities and training of midwives in conducting childbirth assistance and knowing about the knowledge of midwives in applying the 58 steps of the APN. The design of this research was a qualitative study approach. It was conducted on December 2018 until January 2019.The informants were 8 people (1 head of community health center, 1 coordinating midwife and 7 village midwives). The data were collected through interviews and observation. It was analyzed in the form of input, process and output variables. The results of this research indicated that the level of knowledge of midwives was not good because there were APN steps that had not been carried out. Then, the attitude of midwives in implementing of Normal Childbirth Care did not base on standards. Next, the midwives who had been participated in APN training, they were more discipline and apply 58 APN steps even though it was not optimal. In short, it can be concluded that midwives in the Tanjung Emas Community Health Center did not taken all the APN steps.Keywords: Application of 58 APN Steps